A curriculum development project for a school nursing certification program in Turkey: A delphi study - KADIOĞLU, HASİBE (My University, 2023)
Objective: School nursing education has not been standardized in Turkey so that it was decided the Delphi technique would be used to develop a curriculum for a program of education in school nursing.Methods: The data were collected from the expert panel via the Delphi technique by means of e-mail. Data were collected in three consecutive Delphi rounds. The population of the study comprised academic nurses and school nurses working in the area of school nursing in Turkey. A total of 83 experts were invited to participate in the study. The data were evaluated in terms of Quartile 1, Quartile 3, medians, interquartile ranges. Interquartile range refers to the difference between Quartile 3 and 1. Consensus was considered as less than the interquartile range of 1.2.Results: At the end of Round-1, 177 learning outcomes, nine main topics, 262 sub-topics were obtained. At the end of Round-2, 167 learning outcomes, nine main and 255 sub-topics were gathered, while at the end of Round-3, agreement was reached regarding nine main topics, 255 sub-topics, 167 learning outcomes, thus ending the Delphi rounds.Conclusions: The curriculum on which agreement was reached will be treated as a guide to school nursing education and contribute to the standardization of this instruction.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; Health Sciences; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Research and Theory; Reviews and References (medical); Certification; curriculum; delphi technique; school nurse education; Certification; curriculum; delphi technique; school nurse education